Association between glucose-to-albumin ratio and ischemic stroke risk in patients with coronary heart disease: a machine learning-based predictive model analysis - Ling Hou; Yuanhong Li; Qianfei Liu (BMC Cardiovascular Disorders)
Abstract Background Coronary heart disease (CHD) and ischemic stroke (IS) share several pathophysiological mechanisms and risk factors, such as hypertension, hyperlipidemia, and diabetes. Investigating novel markers, such as the glucose-to-albumin ratio (GAR), for predicting the risk of IS in CHD patients holds significant clinical value. Methods We retrospectively enrolled 1,885 patients diagnosed with CHD who were treated at our hospital from January 1, 2022, to July 31, 2024. Feature selection was conducted using the Boruta algorithm, and a multilayer perceptron (MLP) model was employed to predict the risk of IS in CHD patients. The performance of the model was evaluated using ROC curves and calibration plots. SHAP values and partial dependence plots (PDP) were used to interpret the model’s predictions. Results The study showed that patients in the IS group were older and had significantly higher rates of hypertension and diabetes compared to those without AIS. Additionally, the AIS group had a higher prevalence of triple-vessel disease and right coronary artery lesions. GAR was significantly elevated in the IS group compared to the non-IS group. Key features identified by the Boruta algorithm included GAR, hyperlipidemia, and a history of hypertension. SHAP analysis indicated that GAR was significantly associated with IS risk, and PDP analysis further confirmed GAR as an independent predictor of IS. Conclusion GAR is a significant independent predictor of IS risk in CHD patients, with elevated GAR levels being strongly associated with an increased risk of IS.